EFFECT OF INSTRUCTIONAL VIDEO OF SPLINTING PROCEDURE TO NURSING STUDENTS SPLINTING SKILL (PREHOSPITAL SETTING) - Rismawan Adi Yunanto; Yuana Dwi Agustin (UNEJ e-Proceeding)
Musculoskeletal injuries (MSI) is one kind ofinjury that is often experienced by people who havean accident (Chalya et al. 2012). Fracture is one ofthe symptom caused by some types of accidentssuch as traffic accidents (45.3%), falls (42.6%),workplace accidents (8.9%), sport accidents (2.2%),or as a result of gun shots (0.89%). The effect ofmusculoskeletal injuries is the emergence ofextreme pain, mobilizing problem, and severebleeding that may also occur depending on thelocation and type of the fracture (Vyas et al. 2014).Research conducted by Mishra and Mishra (2015)showed that in 30% of patients who had an accident,18% had a single fracture, while some patients hadmultiple fractures. The complications due tofractures can be a serious problem such as malunion,nonunion, pain, loss of function, muscle atrophy,cartilage degeneration, stiff / swollen joint, deepvein thrombosis (DVT), pulmonary embolism (PE),and died due to massive bleeding (Mehta et al.2014).Prehospital care and transportation for patientswho had fracture must done immediately in order toprevent the injured bone getting worse and canreduce the extreme pain which emerged as a resultof fracture (El-Dakhakhny, 2010). Splinting is one ofthe procedure that is given with the purpose to givean immobilization in a patient (Irajpour et al. 2012).As a simple technique, splinting procedure is veryeasy to do as an effective option that highly effectivein the treatment of patient with fracture on theemergency situation (Alton et al. 2014). Splintingprocedure is quite simple, but it require a form ofunderstanding and set of skills to do correctly.Nursing students have a very important role inassisting the process of handling victims who issuffering from fracture. They also need to have aspecial skill in doing a splinting procedure. Aninnovative teaching method using technology is veryimportant for nursing student to master the splintingprocedure effectively (Parasuram et al. 2014).One of the strategies of innovative learningmodel based on modern technology is an audiovisualinstructional video that gives a real applicationconcept of nursing procedure or other nursingexperience in a video form (Jenson & Forsyth, 2012).The use of this model will provide an understandingof the concept for nursing students independently togain the knowledge and also the set of skills (Cant &Cooper, 2010). Smith and Hamilton (2015) in theirresearch on the effects of instructional video as oneof strategies of learning in nursing student showedthat the model of learning with instructional videoprovided convenience for nursing students toenhance clinical skills for the basic competencies innursing.The purpose of this study is to determine theeffect of instructional video of splinting procedure tonursing students splinting skill.